(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
Integration of the Russian economy into the international business space is a continuous and inevitable process. The article is devoted to questions concerning the place of the Russian economy in the world and readiness of domestic management for competitive struggle with the foreign companies